Valuing Coral Reef Preservation in a Caribbean Marine Protected Area. Economic Impact of Scuba Diving in Corals of Rosario and San Bernardo National Natural Park, Colombia - Trujillo, Juan C. (2017)
This study estimates the economic value of scuba diving services in the Corals of Rosario and San Bernardo National Natural Park, Colombia. Although this park attracts a high number of divers, dredging of an adjacent channel threatens the sustainability of its reefs system. Using the travel cost method, we apply truncated count data models to estimate demand for scuba diving services. We estimate the annual benefit of diving services and consumer surplus for both domestic and foreign divers. The estimates obtained can be used to inform further assessments of the value of recreational scuba diving in these coral reefs.